Factors associated with early sexual debut in Slovenia: results of a general population survey. Issue 6 (6th December 2006) - Klavs, I; Rodrigues, L C; Weiss, H A; Hayes, R
Abstract : Objectives: To investigate time trends in age at first heterosexual intercourse (FHI) and associated factors. Methods: Data were collected from a national probability sample of the general population aged 18–49 years. Results: Median age at FHI was 17 years for men and 18 years for women, but declined from 18 years to 17 years in men born after the early 1960s and in women born after the early 1970s. Early FHI (before age 16) was reported by 15.2% of men and 7.4% of women, but in recent cohorts (born 1975–82), proportions were similar in both sexes (16.9% and 14.4%, respectively). In women, higher educational level and acquiring most knowledge about sex from parents or in school were associated with later age at FHI. Half the women with early FHI judged the event to have occurred too soon. 4.2% of women with early FHI reported coercion at FHI, compared to 0.9% overall. The main factor associated with early FHI in men was not living with both parents up to the age of 15. Individuals with early FHI were more likely to report higher risk sexual behaviour as well as teenage motherhood and, for men, not having used a condom at FHI and bacterial sexually transmitted infections. Three in four individuals with early FHI thought they had inadequate sexual knowledge at FHI. Many would have liked to have learned more from parents and in school. Conclusions: Improved sexual education among young Slovenians should aim to delay FHI until a more mature age and to be better prepared for safer sex.